The economic impact of ageing populations in the EU25 member states - Carone, Giuseppe; Costello, Declan; Guardia, Diez N.; Mourre, Gilles; Przywara, Bartosz; Salomaki, Aino.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
This paper presents an assessment of the overall economic impact of ageing for the EU Member States. It draws upon the macroeconomic assumptions developed by the Ageing Working Group attached to the Economic Policy Committee and the Directorate General for Economic and Financial Affairs for the purpose of making age-related expenditure projections. The paper presents and analyses projections of the impact of ageing populations on the labour market using a refined cohort approach by age and gender, as well as projections for potential economic growth rates up to 2050.
Economic Papers